2020
DOI: 10.23937/2378-2951/1410190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the SARS-Cov-2 Virus Pandemic on Children and Adults with Congenital Heart Disease: Its Burden and Risk Factors

Abstract: The novel coronavirus causes severe acute respiratory syndrome 2, and can infect any population. With the currently available information on the behavior of the pandemic, we conclude that the virus has come to stay. It is clear that the most aggressive behavior and worst outcome of the infection occurs in already established risk groups, such as those with cardiovascular disease. Those with congenital heart disease make up a special risk group. Due to this group's high heterogeneity and the paucity of publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…6,[9][10][11] Previous reports suggest age, obesity, type 1 diabetes, genetic disorders, immunosuppression, chronic pulmonary disease, and Latino, Hispanic, or Black racial or ethnic identification may place paediatric and young adult patients at higher risk for more severe illness and hospitalisation. 7,[10][11][12][13][14][15] While clinical evidence suggests that underlying cardiovascular disease increases the risk for severe coronavirus disease 2019 illness, hospitalisation, and death in adult patients, [16][17][18] clarity on the role of underlying congenital heart disease and other paediatric-onset chronic cardiovascular conditions has been slower to emerge. While several studies of mostly adult patients with underlying congenital heart disease showed very rare hospitalisations and deaths due to coronavirus disease 2019 infection, 19,20 more recent data from a large database of over 800 hospitals in the United States found an association between diagnostic codes for congenital cardiac and circulatory anomalies and increased risk of severe disease and hospitalisation in patients under 18 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…6,[9][10][11] Previous reports suggest age, obesity, type 1 diabetes, genetic disorders, immunosuppression, chronic pulmonary disease, and Latino, Hispanic, or Black racial or ethnic identification may place paediatric and young adult patients at higher risk for more severe illness and hospitalisation. 7,[10][11][12][13][14][15] While clinical evidence suggests that underlying cardiovascular disease increases the risk for severe coronavirus disease 2019 illness, hospitalisation, and death in adult patients, [16][17][18] clarity on the role of underlying congenital heart disease and other paediatric-onset chronic cardiovascular conditions has been slower to emerge. While several studies of mostly adult patients with underlying congenital heart disease showed very rare hospitalisations and deaths due to coronavirus disease 2019 infection, 19,20 more recent data from a large database of over 800 hospitals in the United States found an association between diagnostic codes for congenital cardiac and circulatory anomalies and increased risk of severe disease and hospitalisation in patients under 18 years of age.…”
Section: Introductionmentioning
confidence: 99%